2013
DOI: 10.1017/s1479262113000294
|View full text |Cite
|
Sign up to set email alerts
|

SSR-based and carotenoid diversity assessment of tropical yellow endosperm maize inbred lines

Abstract: Yellow endosperm maize can be used to reduce vitamin A deficiency among many pre-school children and women of reproductive age in sub-Saharan Africa. Assessment of the genetic diversity of tropical yellow endosperm maize inbred lines will have genetic gains in breeding design to develop lines with an enhanced level of provitamin A. We screened 122 tropical yellow endosperm maize inbred lines with 62 simple sequence repeat (SSR) markers and 51 SSR loci were polymorphic. We detected 190 alleles with an average o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…Adeyemo, Menkir, Gedil and Omidiji () studied the genetic diversity in maize inbred lines using AFLP and SSR molecular markers. Results showed that the genetic distance (GD) was varied from 0.08 to 0.64 for AFLP markers and from 0.007 to 0.59 for SSR markers for pairwise interaction of inbred lines.…”
Section: Breeding Strategies For Provitamin a Biofortification Of Maizementioning
confidence: 99%
See 1 more Smart Citation
“…Adeyemo, Menkir, Gedil and Omidiji () studied the genetic diversity in maize inbred lines using AFLP and SSR molecular markers. Results showed that the genetic distance (GD) was varied from 0.08 to 0.64 for AFLP markers and from 0.007 to 0.59 for SSR markers for pairwise interaction of inbred lines.…”
Section: Breeding Strategies For Provitamin a Biofortification Of Maizementioning
confidence: 99%
“…Correlations between carotenoid‐based clustering and molecular marker‐based clustering were not strong. It is recommended that molecular analysis be used for the selection of parents for biparental crosses, whereas GD be used for the selection of parents for broadening the genetic base (Adeyemo et al., ). Das and Singh () used SSR markers to dissect the molecular diversity in yellow maize genotypes, and observed that Jaccard's similarity coefficients were ranged from 0.17 to 0.97.…”
Section: Breeding Strategies For Provitamin a Biofortification Of Maizementioning
confidence: 99%
“…Such varieties could be used in the development of yellow endosperm maize varieties (Open Pollinated Varieties and hybrids) which possess genes for adaptation and superior agronomic performance and thus represent a good genetic base to breed tropical maize for high levels of pro-vitamin A carotenoids [12]. In two separate studies, [13] as well as [14] assessed the nature and extent of the genetic diversity among tropically adapted yellow endosperm maize inbred lines at the International Institute of Tropical Agriculture (IITA) maize breeding programme. In the first study, [13] noted the diversity of carotenoid contents among 38 tropically adapted yellow endosperm maize inbred lines while the second report [14] contained information on the nature of variability for different carotenoid contents among the newly developed 122 inbred lines and grouped into three major groups based on carotenoid contents.…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellites (simple sequence repeats, SSR) are widely used to evaluate genetic diversity and population structure based on their multiallelic nature; they can produce many alleles per locus, abundance and are repeatable (Warburton et al, 2008). SSR markers have been applied to characterize the genetic relationships of yellow adapted tropical maize germplasm from IITA breeding programs in Nigeria (Adeyemo and Omidiji, 2014). Also, a number of previous studies have reported the genetic diversity, genetic relationship and population structure of diverse maize inbred lines, breeding materials and maize landraces from the different maize germplasm and breeding programs based on SSR data (Inghelandt et al, 2010;Zhi-zhai et al, 2010;Semagn et al, 2014;Bedoya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%